Solid pseudopapillary neoplasm of the pancreas showing marked distal atrophy: A case report. (2019) - Tsujie, Masanori; Wakasa, Tomoko; Mizuno, Shigeto; Ishikawa, Hajime; Manabe, Hironobu; Koyama, Taichi; Kitani, Kotaro; Satoi, Shumpei; Inoue, Keisuke; Fukuda, Shuichi; Kawasaki, Toshihiko; Yukawa, Masao; et al.
Highlights: Solid pseudopapillary neoplasm with marked parenchymal atrophy of the distal pancreas. No acinar cells were observed, indicating exocrine dysfunction of atrophic parenchyma. The vestige of main pancreatic duct was observed in the distal atrophic pancreas. Central pancreatectomy without anastomosis of distal side of pancreas was performed. Abstract: Introduction: Solid pseudopapillary neoplasm (SPN) of the pancreas is a rare neoplasm, affecting primarily young females. Because SPNs are of low-malignancy, they rarely obstruct the main pancreatic duct (MPD) and cause atrophy of the distal pancreas even if their tumor sizes are large. Presentation of case: A 35-year-old female was referred to our hospital due to pancreatic tumor. Imaging findings showed the presence of well-defined round tumor in the body of the pancreas with 25-mm in diameter. The pancreas parenchyma distal to the tumor was markedly atrophic, and MPD dilatation was not observed. The lesion was diagnosed as SPN by endoscopic ultrasound-guided fine needle aspiration (EUS-FNA), and central pancreatectomy was performed. Intraoperative frozen section of the distal atrophic pancreas showed no evidence of acinar cells, indicating exocrine dysfunction. Therefore, we closed distal pancreas stump instead of reconstruction. In the distal atrophic parenchyma, scattered foci of islets of Langerhans and the vestige of dilated MPD were observed. She has shown neither endocrine nor exocrine insufficiency after surgery. Discussion: SPNs are usually found without atrophic change of distal pancreas. To the best of our knowledge, this is the first report of SPN in which exocrine dysfunction of atrophic pancreas was demonstrated pathologically and central pancreatectomy without anastomosis of distal pancreas was chosen for the surgical treatment. Conclusion: We reported a very rare case of SPN with marked distal parenchymal atrophy. We successfully performed central pancreatectomy without reconstruction.